Anthracene azepine material and preparation method and application thereof
By introducing the structural design of anthracene and azazole materials into OLED materials, the shortcomings of existing OLED materials in dark blue light luminescence efficiency and color purity are solved, and the color purity and service life are achieved, while improving luminescence efficiency.
Patent Information
- Application Number
- CN202411793509.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-09
AI Technical Summary
Existing OLED materials have limitations in terms of luminous efficiency and color purity, especially in the field of deep blue light, which affects the performance and life of the device.
Anthracene and azazole materials are used, and their structural design includes anthracene, deuterated carbazole and hazole structures. The spin-orbit coupling effect is enhanced through the molecular structure of large steric hindered space twist, restrict molecular relaxation, and realize deep blue light emission. .
It significantly improves the color purity and service life of the dark blue base color of OLED devices, and at the same time improves the luminous efficiency, providing deep blue light materials with superior comprehensive performance.
Smart Images

Figure CN119264141B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an anthracene azepine material and a preparation method and application thereof, belonging to the technical field of OLED luminescent materials. Background Art
[0002] OLED (Organic Light Emitting Display) refers to the phenomenon that organic semiconductor materials and luminescent materials emit light through carrier injection and recombination under the drive of an electric field.
[0003] OLED can be used in the fields of display and lighting. It is the third generation of display technology based on electroluminescence after CRT picture tubes and LCD liquid crystal displays. Compared with the previous two generations of display technology, OLED display panels truly possess the characteristics of "future technology" materials, such as lightness, thinness, fast response, transparent display, and flexible foldability. Its special structure does not require heavy vacuum devices and additional screen backlight sources and liquid crystal phases. It only needs to evaporate the luminescent material onto a thin ITO glass plate, and it can emit light and color when powered on. At the same time, OLED has a wider color gamut, a larger viewing angle, a wider operating temperature range, and lower power consumption. According to the driving method, OLED can be divided into active drive and passive drive. The former has more advantages in energy consumption, display quality, and life cycle, so it has become a mainstream application.
[0004] Although OLED displays have many advantages, there are still many aspects that need to be improved. The current development direction of the entire display industry, especially liquid crystal display technology, is "three highs and two lows", namely "high brightness, high contrast, high refresh rate, low power consumption, and low cost." However, the current OLED materials have certain limitations in their luminous efficiency and color purity, and the materials are extremely scarce in the deep blue light field. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides an anthracene azapine material and a preparation method and application thereof. The anthracene azapine material is used in an OLED device to significantly improve the color purity and service life of the device's deep blue primary color.
[0006] The technical solution of the present invention to solve the above technical problems is as follows: an anthracene azopyridine material, the structure of the anthracene azopyridine material is shown in the following formula:
[0007] ;
[0008] The R is any one of a deuterated terphenyl group, an isoquinolyl group, a pyryl group, a 9,9-diphenylfluorenyl group, a dibenzothienyl group, and a deuterated N-phenylcarbazolyl group.
[0009] Furthermore, the R is any one of the following structural formulas:
[0010] .
[0011] Furthermore, the structural formula of the anthracene azepine material is any one of the following structural formulas:
[0012] .
[0013] The present invention also discloses a method for preparing anthracene azepine materials, the preparation method comprising:
[0014] ;
[0015] S1. Under the protection of inert gas, N-bromosuccinimide and 1,5-difluoroanthracene are reacted in an organic solvent at a reaction temperature of 5-10° C. After the reaction is completed, compound A is obtained by post-treatment;
[0016] Under the protection of inert gas, 1-chlorocarbazole and solvent are added to the reactor, stirring is started, and then heavy water, deuterated sulfuric acid, and tetrabutylammonium bromide are added, stirring and heating are carried out to carry out hydrogen-deuterium replacement reaction. After the reaction is completed, compound B is obtained by post-treatment;
[0017] S2. Under the protection of inert gas, compound A, compound B, sodium tert-butoxide, and catalysts tris(dibenzylideneacetone)dipalladium and 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl are added to the reactor, and then xylene is added. The temperature is raised to 120-130° C. and the reaction is kept warm. After the reaction is completed, compound C is obtained by post-treatment.
[0018] S3, under the protection of inert gas, compound C, benzophenone imine, sodium tert-butoxide, and catalysts palladium acetate and 2-dicyclohexylphosphino-2',6'-dimethoxybiphenyl are sequentially added to the reactor, and then toluene is added, and the temperature is raised to 100-1100° C. and the reaction is kept warm. After the reaction is completed, compound D is obtained by post-treatment;
[0019] S4, under the protection of inert gas, compound D, cesium carbonate and N,N-dimethylformamide are mixed evenly, and the mixture is kept warm at 120-140° C. for reaction. After the reaction is completed, compound E is obtained by post-treatment;
[0020] S5. Under the protection of inert gas, compound E, deuterated fluorobenzene, cesium carbonate and N,N-dimethylformamide are mixed evenly, and the mixture is kept warm at 140-145° C. for reaction. After the reaction is completed, compound F is obtained by post-treatment.
[0021] S6. Under the protection of inert gas, compound F reacts with XR under alkaline conditions. After the reaction, post-treatment is performed to obtain the anthracene azepine material, wherein X is any one of Cl, Br, I, and F.
[0022] The invention also discloses an application of an anthracene azapine material, wherein the anthracene azapine material is applied to an organic electroluminescent device.
[0023] Furthermore, the anthracene azepine material is applied to the light-emitting layer of an organic electroluminescent device.
[0024] Furthermore, the anthracene azepine material is used as the main light-emitting material in the light-emitting layer of an organic electroluminescent device. The prepared organic electroluminescent device has deep blue light characteristics, which can improve the light-emitting performance of the light-emitting device; the light-emitting performance can be current utilization efficiency, driving voltage size and light-emitting life of the device.
[0025] The beneficial effects of the present invention are:
[0026] The anthracene azapine material of the present invention has a parent structure of anthracene, deuterated carbazole, heterocyclic structure, etc. The structure with large steric hindrance and spatial distortion in the molecule significantly increases the spin-orbit coupling between different excited states, so that the relaxation of the molecule is greatly restricted, and the device finally realizes deep blue light emission. The introduced aromatic heterocyclic structure can greatly improve the stability of the material, and the deuterated structure can significantly improve the device life and light emission efficiency.
[0027] The organic light-emitting device made of the anthracene azepine material of the present invention has high color purity, good luminescence life and stability, is a deep blue light material with excellent comprehensive performance, and can have good application prospects in the rapidly developing OLED industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a schematic structural diagram of the organic electroluminescent device described in the embodiment;
[0029] In the figure, 1, transparent substrate layer; 2, transparent anode electrode layer; 3, hole injection layer; 4, hole transport layer; 5, electron blocking layer; 6, light-emitting layer; 7, hole blocking layer; 8, electron transport layer; 9, electron injection layer; 10, cathode reflective electrode layer. DETAILED DESCRIPTION
[0030] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.
[0032] 1. Preparation Example
[0033] The common intermediate compound F was prepared by the following specific synthesis method:
[0034] ;
[0035] The preparation of compound F comprises the following steps:
[0036] (1) Under the protection of inert gas, N-bromosuccinimide (NBS) was slowly added to the mixed solution containing 1,5-difluoroanthracene and dichloroethane in a three-necked flask, and the mixture was cooled to 7.0°C under stirring to react. The molar ratio of N-bromosuccinimide to 1,5-difluoroanthracene was 2.3eq:1.0eq. The mixture was kept at 7.0°C for reaction. After the reaction was complete, the mixture was hydrolyzed, extracted, washed with water, passed through a column, desolvated, and recrystallized to obtain a yellow solid compound A with a total yield of 82.7% and GC of ≥99.0%. GC-MS: theoretical value: 372.00, measured value: 371.59.
[0037] The NMR data of compound A is:
[0038] 1 H NMR (500 MHz, Chloroform-d) δ 8.07 (dd, 2H), 7.50 (td, 2H), 7.22(td,2H).
[0039] (2) Under the protection of inert gas, 1-chlorocarbazole and mesitylene were added to the three-necked flask in sequence, and stirring was started. Then, heavy water, deuterated sulfuric acid, and tetrabutylammonium bromide were added. The mixture was stirred and heated to 140.0°C for 10 hours for hydrogen-deuterium replacement reaction. After the reaction was completed, the aqueous phase was separated. The hydrogen-deuterium replacement reaction was carried out twice in the same reaction mode. The mass ratio of 1-chlorocarbazole, heavy water, deuterated sulfuric acid and tetrabutylammonium bromide was 1.0kg:4.0kg:4.0kg:3.5kg. After the three hydrogen-deuterium replacement reactions were completed, saturated ammonium chloride aqueous solution was first added for quenching, and then hydrolysis, extraction, water washing, column chromatography, solvent removal, and recrystallization were performed to obtain an off-white solid compound B with a total yield of 75.2% and GC of ≥99.0%. GC-MS: theoretical value: 208.69, measured value: 208.50. The deuterium replacement rate was 87.5%.
[0040] The NMR data of compound B are:
[0041] 1 H NMR (500 MHz, Chloroform-d) δ 9.87 (s, 1H).
[0042] (3) Under the protection of inert gas, compound A, compound B, sodium tert-butoxide, and catalyst tris(dibenzylideneacetone)dipalladium, 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl were added to a three-necked flask in sequence, followed by xylene. The temperature was raised to 125.0°C. The molar ratio of compound A, compound B and sodium tert-butoxide was 1.0eq:2.2eq:3.0eq. The reaction was kept warm for 12.0h until the reaction was qualified. After extraction, washing, column column, solvent removal, and recrystallization from chlorobenzene, an off-white solid compound C was obtained. The total yield was 85.5%, HPLC: ≥99.5%. HPLC-MS: theoretical value: 627.57, measured value: 627.09.
[0043] The NMR data of compound C are:
[0044] 1H NMR (500 MHz, Chloroform-d) δ 7.95(dd, 2H), 7.45(td, 2H), 7.07(td, 2H).
[0045] (4) Under the protection of inert gas, compound C, benzophenone imine, sodium tert-butoxide, catalyst palladium acetate, 2-dicyclohexylphosphino-2',6'-dimethoxybiphenyl were added to a three-necked flask in sequence, and then toluene was added. The temperature was raised to 105.0°C. The molar ratio of compound A, compound B and sodium tert-butoxide was 1.0eq: 2.5eq: 3.0eq. The reaction was kept warm for 5.0h and the reaction was qualified. After extraction, water washing, acidification, pulping, alkalization, column chromatography, solvent removal, and recrystallization, an off-white solid compound D was obtained with a total yield of 81.2%, HPLC: ≥99.5%. HPLC-MS: theoretical value: 588.71, measured value: 588.56.
[0046] The NMR data of compound D are:
[0047] 1 H NMR (500 MHz, Chloroform-d) δ 7.88 (dd, 2H), 7.45 (td, 2H), 7.06(td, 2H), 5.87(m,4H).
[0048] (5) Under the protection of inert gas, compound D, cesium carbonate and N,N-dimethylformamide (DMF) were mixed evenly, the molar ratio of compound D to cesium carbonate was 1.0eq:5.0eq, and the mixture was kept at 130.0°C for 6 hours to complete the reaction. After post-treatment, the white solid compound E was obtained by filtration, solvent removal, extraction, water washing, column chromatography and recrystallization, with a total yield of 84.0%, HPLC ≥ 99.5%. HPLC-MS: theoretical value: 548.68, measured value: 548.26.
[0049] The NMR data of compound E are:
[0050] 1 H NMR (500 MHz, Chloroform-d) δ 8.61 (s, 2H), 7.86 (dd, 2H), 7.37(t, 2H), 7.23 (dd, 2H).
[0051] (6) Under the protection of inert gas, compound E, deuterated fluorobenzene, cesium carbonate, and N,N-dimethylformamide (DMF) were mixed evenly. The molar ratio of compound E, deuterated fluorobenzene, and cesium carbonate was 1.0eq:0.95eq:1.5eq. The mixture was kept at 142.0°C for 10 h to complete the reaction. After post-treatment, the off-white solid compound F was obtained by filtration, solvent removal, extraction, water washing, column chromatography, and recrystallization. The total yield was 61.2%, and the HPLC was ≥99.9%. HPLC-MS: theoretical value: 629.82, measured value: 629.17.
[0052] The NMR data of compound F are:
[0053] 1 H NMR (500 MHz, Chloroform-d) δ 8.63 (s, 1H), 7.88 (dd, 1H), 7.83 (dd, 1H), 7.44 (m, 3H), 7.21 (dd, 1H).
[0054] Example 1
[0055] Synthesis of compound 1:
[0056] ;
[0057] Under the protection of inert gas, 62.9g (0.1mol) of compound F, 26.1g (0.1mol) of 3-fluoroterphenyl-D13, and 97.5g (0.3mol) of cesium carbonate were weighed in a 2L three-necked flask, and then 629.0g of N,N-dimethylformamide (DMF) was added. Stirring was started and the temperature was raised to 125.0℃. The reaction was kept warm for 15.0h and the result was qualified. HPLC: 92.1%. After extraction, water washing, column column, solvent removal, and toluene recrystallization, 76.1g of light yellow solid compound 1 was obtained, with a total yield of 87.4%, HPLC: 99.9%. HPLC-MS: theoretical value: 871.19, measured value: 871.02.
[0058] The NMR data of compound 1 are:
[0059] 1H NMR (500 MHz, Chloroform-d) δ 7.86 (dd, 2H), 7.41 (dt, 2H), 7.28(ddd, 2H).
[0060] Example 2
[0061] Synthesis of compound 3:
[0062] ;
[0063] Under the protection of inert gas, 62.9g (0.1mol) of compound F, 20.8g (0.1mol) of 8-bromoisoquinoline, 19.2g (0.2mol) of sodium tert-butoxide, 0.915g (1.0mmol) of tris (dibenzylideneacetone) dipalladium, and 0.952g (2.0mmol) of 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl were added to a 2L three-necked flask in sequence, and then 943.5g of xylene was added, and the temperature was raised to 125.0℃. The reaction was kept warm for 12.0h and the reaction was qualified, HPLC: 90.2%. After extraction, washing, column, and recrystallization from chlorobenzene, 65.1g of off-white solid compound 3 was obtained, with a total yield of 86.0%, HPLC: 99.9%. HPLC-MS: theoretical value: 756.96, measured value 756.80.
[0064] The NMR data of compound 3 are:
[0065] 1 H-NMR(500MHz, Chloroform-d): δ 9.32 (s, 1H), 8.53 (d, 1H), 7.84(dd,2H), 7.66(ddd, 2H), 7.50 (t, 1H), 7.38 (m, 3H), 7.30 (dd, 1H), 7.25(dd, 1H),
[0066] Example 3
[0067] Synthesis of compound 5:
[0068] ;
[0069] Under the protection of inert gas, 62.9g (0.1mol) of compound F, 28.1g (0.1mol) of 2-bromopyrene, 19.2g (0.2mol) of sodium tert-butoxide, 0.915g (1.0mmol) of tris(dibenzylideneacetone)dipalladium, and 0.952g (2.0mmol) of 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl were weighed in a 2L three-necked flask, and then 943.5g of xylene was added. The temperature was raised to 125.0℃, and the reaction was kept warm for 12.0h. The reaction was qualified, HPLC: 90.2%. After extraction, washing, column, and recrystallization from chlorobenzene, 70.8g of off-white solid compound 5 was obtained, with a total yield of 85.1%, HPLC: 99.8%. HPLC-MS: theoretical value: 829.40, measured value: 830.01.
[0070] The NMR data of compound 5 are:
[0071] 1 H NMR (500 MHz, Chloroform-d) δ 8.13 (dd, 1H), 8.00 (t, 1H), 7.84(dd,2H), 7.74(dd, 2H), 7.60 (dd,2H), 7.40 (m, 4H), 7.30 (dd, 1H), 7.24 (dd,1H).
[0072] Example 4
[0073] Synthesis of compound 9:
[0074] ;
[0075] Under the protection of inert gas, 62.9g (0.1mol) of compound F, 39.3g (0.1mol) of 2-bromo-9,9-diphenyl-9H-fluorene, 19.2g (0.2mol) of sodium tert-butoxide, 0.915g (1.0mmol) of tris(dibenzylideneacetone)dipalladium, and 0.952g (2.0mmol) of 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl were weighed in a 2L three-necked flask, and then 943.5g of xylene was added, the temperature was raised to 125.0℃, and the reaction was kept warm for 12.0h. The reaction was qualified, HPLC: 94.3%. After extraction, water washing, decolorization, column column, and recrystallization, 84.7g of off-white solid compound 9 was obtained, with a total yield of 89.5%, HPLC: 99.9%. HPLC-MS: theoretical value: 946.22, measured value: 945.93.
[0076] The NMR data of compound 9 are:
[0077] 1H NMR (500 MHz, Chloroform-d) δ 7.84 (d, 1H), 7.82 (dd,2H), 7.61 (d,1H), 7.40 (m, 2H), 7.35 (m, 1H), 7.30 (dd, 1H),7.29 (m, 2H), 7.28 (d, 2H),7.27 (d, 2H), 7.23(ddd, 2H), 7.22 (m, 1H), 7.12(q,3H),7.10(d, 2H), 6.87 (d,1H).
[0078] Example 5
[0079] Synthesis of compound 12:
[0080] ;
[0081] Under the protection of inert gas, 62.9g (0.1mol) of compound F, 20.2g (0.1mol) of 1-fluorodibenzothiophene, and 97.5g (0.3mol) of cesium carbonate were weighed in a 2L three-necked flask, and then 629.0g of N,N-dimethylformamide (DMF) was added. Stirring was started and the temperature was raised to 125.0℃. The reaction was kept warm for 15.0h and the result was qualified. HPLC: 94.7%. After extraction, washing, column column, and dioxane recrystallization, 72.2g of off-white solid compound 12 was obtained, with a total yield of 88.9%, HPLC: 99.9%. HPLC-MS: theoretical value: 812.06, measured value: 811.89.
[0082] The NMR data of compound 12 are:
[0083] 1 H NMR (500 MHz, Chloroform-d) δ 8.11 (dd, 1H), 7.84 (dd, 2H), 7.75(dd, 1H), 7.52 (dd,1H), 7.45 (m, 1H), 7.41(d, 1H), 7.40 (m, 2H), 7.33 (td,1H), 7.30 (dd,1H),7.27 (dd,1H), 7.18 (dd, 1H).
[0084] Example 6
[0085] Synthesis of compound 14:
[0086] ;
[0087] Under the protection of inert gas, 62.9g (0.1mol) of compound F, 33.4g (0.1mol) of 3-bromo-N-phenylcarbazole-D12, 19.2g (0.2mol) of sodium tert-butoxide, 0.915g (1.0mmol) of tris(dibenzylideneacetone)dipalladium, and 0.952g (2.0mmol) of 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl were added to a 2L three-necked flask in sequence, and then 813g of xylene was added. The temperature was raised to 125.0℃ and the reaction was kept warm for 12.0h. The reaction was qualified, HPLC: 90.2%. After extraction, washing, column column, and recrystallization from chlorobenzene, 58.9g of off-white solid compound 14 was obtained, with a total yield of 88.7%, HPLC: 99.9%. HPLC-MS: theoretical value: 883.18, measured value: 883.04.
[0088] The NMR data of compound 14 are:
[0089] 1 H NMR (500 MHz, Chloroform-d) δ 7.85 (dd, 2H), 7.40 (dt, 2H), 7.31 (dd, 1H), 7.26 (dd, 1H).
[0090] The synthesis methods of other compounds included in the present invention are the same or similar to those of the specific implementation examples, and are not listed one by one. The mass-to-core ratios of the synthesized compounds are shown in Table 1 below; the main raw materials and some auxiliary materials used to synthesize the compounds of the specific implementation examples are all known compounds, and the specific CAS numbers are shown in Table 2.
[0091] Table 1 Mass-to-nuclear ratio of compounds
[0092]
[0093] Table 2 CAS numbers of relevant main raw materials and auxiliary materials
[0094]
[0095] 2. Preparation and evaluation of organic electroluminescent devices
[0096] The following comparative example 1 and application examples 1-6 illustrate in detail the application effect of the OLED light-emitting material synthesized by the present invention on the device. The specific structural formula of the compound involved is shown in the figure below:
[0097] ;
[0098] Comparative Example 1
[0099] The structure of organic electroluminescent devices is as follows Figure 1As shown, the transparent anode electrode layer 2 (film thickness of 208nm, indium tin oxide) with the transparent substrate layer 1 is processed: first, photolithography and etching are performed to form the required regular anode electrode layer 2, and then the glass transparent substrate layer 1 is washed, that is, alkaline washing, deionized water washing, acetone ultrasonic cleaning, ethanol ultrasonic cleaning, ultrapure water cleaning, drying, and then ultraviolet-ozone washing of the transparent anode electrode layer 2 is performed to ensure that the organic residues on the surface of the transparent anode electrode layer 2 are removed. After the above treatment, the hole injection layer 3 is evaporated on the transparent anode electrode layer 2, and the structural formula (mCP) material is evaporated using a vacuum evaporation device (evaporation conditions are: using a molybdenum crucible, evaporation speed 0.1nm / s, vacuum degree 4.0*10 -5 Pa), with a film thickness of 56nm. This layer of organic material is used as a hole injection layer 3. The hole injection layer 3 is then vapor-deposited with a 24nm thick material of structural formula two (α-NPB) as a hole transport layer 4. The hole transport layer 4 is then vapor-deposited with a 22nm thick material of structural formula three (TCTA) as an electron blocking layer 5.
[0100] After the electron blocking layer 5 is evaporated, the structural formula tetrakis (DMPPP) material and [2-(4,6-difluorophenyl)pyridine-C2,N] (pyridine) iridium (Firpic) are mixed at a doping weight ratio of 93:7 and then evaporated onto the empty electron blocking layer 5 (evaporation conditions: using a molybdenum crucible, evaporation speed 0.1nm / s, vacuum degree 4.0*10 -5 Pa) to obtain the light-emitting layer 6, the light-emitting layer 6 has a film thickness of 32 nm.
[0101] The preparation of the hole blocking layer 7 is to continue to vacuum-evaporate the hole blocking layer 7 material (the material shown in structural formula five (TmPyPB)) onto the light-emitting layer 6 after the light-emitting layer 6 (evaporation conditions are: using a molybdenum crucible, evaporation rate 0.1nm / s, vacuum degree 4.0*10-5Pa), and the vacuum-evaporated film thickness of the material is 22nm. After the evaporation is completed, the material shown in structural formula six (DPyPA) is evaporated to obtain the electron transport layer 8, and the evaporated film thickness is 80nm. The electron injection layer 9 is formed on the electron transport layer 8 by vacuum evaporation equipment to form a lithium fluoride (LiF) layer with a film thickness of 0.8nm as the electron injection layer 9.
[0102] On the electron injection layer 9, a cathode reflective electrode layer 10 is formed by vacuum deposition. The cathode reflective electrode layer 10 is an aluminum (Al) layer having a film thickness of 148 nm.
[0103] After the organic OLED electroluminescent device is completed as described above, the anode and cathode are connected using a known driving circuit, and then the current-voltage performance, luminous efficiency and luminous spectrum of the device are measured.
[0104] Application Example 1
[0105] An organic electroluminescent device was prepared by the same method as in Comparative Example 1, except that the main light-emitting material (structural formula 4) used in the light-emitting layer 6 of the organic electroluminescent device was changed to the compound 1 of the present invention.
[0106] Application Example 2
[0107] An organic electroluminescent device was prepared by the same method as in Comparative Example 1, except that the main light-emitting material (structural formula 4) used in the light-emitting layer 6 of the organic electroluminescent device was changed to the compound 3 of the present invention.
[0108] Application Example 3
[0109] An organic electroluminescent device was prepared by the same method as in Comparative Example 1, except that the main light-emitting material (structural formula 4) used in the light-emitting layer 6 of the organic electroluminescent device was changed to the compound 5 of the present invention.
[0110] Application Example 4
[0111] An organic electroluminescent device was prepared by the same method as in Comparative Example 1, except that the main light-emitting material (structural formula 4) used in the light-emitting layer 6 of the organic electroluminescent device was changed to the compound 9 of the present invention.
[0112] Application Example 5
[0113] An organic electroluminescent device was prepared by the same method as in Comparative Example 1, except that the main light-emitting material (structural formula 4) used in the light-emitting layer 6 of the organic electroluminescent device was changed to the compound 12 of the present invention.
[0114] Application Example 6
[0115] An organic electroluminescent device was prepared by the same method as in Comparative Example 1, except that the main light-emitting material (structural formula 4) used in the light-emitting layer 6 of the organic electroluminescent device was changed to the compound 14 of the present invention.
[0116] Application Examples 1-6 and Comparative Example 1 have the same brightness (1000cd / m 2 ), the test results under the same external environment temperature (22.0℃) and the same humidity (35.0%) are shown in Table 3.
[0117] Table 3 Test results
[0118]
[0119] According to the data comparison in Table 3, the compounds obtained in the present invention (Application Examples 1-6) have excellent comprehensive performance and great potential for commercial promotion and application. The unique structural design of the anthracene azepine material of the present invention enhances the spin-orbit coupling effect in its molecule, which is conducive to the generation of light. At the same time, the introduction of deuterium atoms delays the half-life of the compound and prolongs its life. Compared with the luminescent properties of existing materials, the organic light-emitting device prepared using the anthracene azepine material of the present invention can obtain a high-deep blue primary color, and has excellent performance in color purity, luminous efficiency and life.
[0120] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0121] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.
Claims
1. An anthracene azepine material, characterized in that: The structure of the anthracene azepine material is shown in the following formula: ; The R is any one of a deuterated terphenyl group, an isoquinolyl group, a pyryl group, a 9,9-diphenylfluorenyl group, a dibenzothienyl group, and a deuterated N-phenylcarbazolyl group.
2. The anthracene azepine material according to claim 1, characterized in that: The R is any one of the following structural formulas: 。 3. The anthracene azepine material according to claim 1, characterized in that: The structural formula of the anthracene azepine material is any one of the following structural formulas: 。 4. A method for preparing an anthracene azepine material according to any one of claims 1 to 3, characterized in that: The preparation method is: ; S1. Under the protection of inert gas, N-bromosuccinimide and 1,5-difluoroanthracene are reacted in an organic solvent at a reaction temperature of 5-10° C. After the reaction is completed, compound A is obtained by post-treatment; Under the protection of inert gas, 1-chlorocarbazole and solvent are added to the reactor, stirring is started, and then heavy water, deuterated sulfuric acid, and tetrabutylammonium bromide are added, stirring and heating are carried out to carry out hydrogen-deuterium replacement reaction. After the reaction is completed, compound B is obtained by post-treatment; S2. Under the protection of inert gas, compound A, compound B, sodium tert-butoxide, and catalysts tris(dibenzylideneacetone)dipalladium and 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl are added to the reactor, and then xylene is added. The temperature is raised to 120-130° C. and the reaction is kept warm. After the reaction is completed, compound C is obtained by post-treatment. S3, under the protection of inert gas, compound C, benzophenone imine, sodium tert-butoxide, and catalysts palladium acetate and 2-dicyclohexylphosphino-2',6'-dimethoxybiphenyl are sequentially added to the reactor, and then toluene is added, and the temperature is raised to 100-1100° C. and the reaction is kept warm. After the reaction is completed, compound D is obtained by post-treatment; S4, under the protection of inert gas, compound D, cesium carbonate and N,N-dimethylformamide are mixed evenly, and the mixture is kept warm at 120-140° C. for reaction. After the reaction is completed, compound E is obtained by post-treatment; S5. Under the protection of inert gas, compound E, deuterated fluorobenzene, cesium carbonate and N,N-dimethylformamide are mixed evenly, and the mixture is kept warm at 140-145° C. for reaction. After the reaction is completed, compound F is obtained by post-treatment. S6. Under the protection of inert gas, compound F reacts with XR under alkaline conditions. After the reaction is completed, post-treatment is performed to obtain the anthracene azepine material, wherein X is any one of Cl, Br, I, and F.
5. A use of an anthracene azepine material according to any one of claims 1 to 3, characterized in that: The anthracene azepine material is applied to the light-emitting layer of an organic electroluminescent device.
6. The use of an anthracene azepine material according to claim 5, characterized in that: The anthraazepine material is used as a main light-emitting material in a light-emitting layer of an organic electroluminescent device.
Citation Information
Patent Citations
Organic electroluminescent device using organic electroluminescent compounds
CN101556990A
Anthracene ether benzimidazole material in ring and application thereof
CN116675705A